The effects of microwave drying combined with other approaches on nuts quality attributes: A review / Azizah Izzati Mohd Sabani and Naemaa Mohamad - Mohd Sabani, Azizah Izzati; Mohamad, Naemaa (2021)
Demand on nuts has been rising globally in recent years due to their good source of protein, healthy fats and nutrients hence providing many benefits to the body's health. To provide a better quality of nuts during processing, transportation and storage, nuts must be dried accordingly to reduce the moisture content, avoid microbial contamination and to avoid post- harvest losses. A suitable method of drying needs to be used to ensure the drying process occurs effectively and give better quality nuts. In this review, microwave drying had been selected due to its benefits of consuming less energy, reducing drying time yet providing an enhanced high-quality product when combined with other approaches for instance microwave drying with surface temperature control, intermittent microwave drying, microwave with ultrasound pre-treatment and microwave assisted solvent extraction. However, the drying method is known for its negative effects on dried product quality such as rancidity. That is why, the effects of microwave drying combined with other approaches on nuts quality attributes such as the drying rate, physicochemical properties, total phenolic content, antioxidant activity and sensorial properties of dried nuts have been discussed. High microwave power will lead to faster drying rate hence reducing the drying time. However, it will lead to higher shrinkage, increment in the total colour change and higher rate of rancidification for the dried nuts. In addition, the total phenolic content and antioxidant activity of nuts treated with microwave drying will increase in parallel with the increase of microwave power. Further study needs to be done regarding the optimizing of microwave drying combined with other drying methods to give a better quality of nuts.